Mediated Dispute Resolution in the Distribution of Outsourced Labor in the Gili Tramena Area - Rahmawati Kusuma; Zaeni Asyhadie (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
This research aims to determine how the resolution of labor disputes through mediation in the outsourcing workforce distribution in the Gili Tramena (Trawangan, Meno and Air) tourism area, as well as the factors influencing the effectiveness of labor dispute resolution through mediation in the outsourcing workforce distribution. The legal status between workers and employers in an employment relationship is said to be the same, but empirically, this juridical fact is difficult to establish. In employment relationships, employers are often